2019
DOI: 10.1186/s13195-018-0454-z
|View full text |Cite
|
Sign up to set email alerts
|

The quest for synergy between physical exercise and cognitive stimulation via exergaming in people with dementia: a randomized controlled trial

Abstract: BackgroundExercise is often proposed as a non-pharmacological intervention to delay cognitive decline in people with dementia, but evidence remains inconclusive. Previous studies suggest that combining physical exercise with cognitive stimulation may be more successful in this respect. Exergaming is a promising intervention in which physical exercise is combined with cognitively challenging tasks in a single session. The aim of this study was to investigate the effect of exergame training and aerobic training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
160
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(170 citation statements)
references
References 72 publications
3
160
2
5
Order By: Relevance
“…Fourteen participants (12%) did not complete the training and were excluded from the analyses. A full description of the reasons for drop-out has been provided previously [6]. Main reasons for drop-out were comorbid medical or physical problems and lack of motivation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen participants (12%) did not complete the training and were excluded from the analyses. A full description of the reasons for drop-out has been provided previously [6]. Main reasons for drop-out were comorbid medical or physical problems and lack of motivation.…”
Section: Resultsmentioning
confidence: 99%
“…Uijen et al / Individual Differences in the Effects of Physical Activity benefit most from physical activity interventions and can help develop individualized training programs accordingly. The objective of this secondary analysis of a previously published randomized controlled trial (RCT) was to examine whether the effect of physical activity on cognitive function in persons with mild to moderate dementia is moderated by patient characteristics [6]. It was hypothesized that combined physical and cognitive exergame training would result in larger improvements in cognitive function than physical training alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies specifically in daycare or residential care settings are scarce. One RCT in PwD attending daycare showed that aerobic training had favorable effects on psychomotor speed only [82]. Altogether, there is a lack of convincing evidence for the efficacy of exercise for cognition in PwD.…”
Section: Effects Of Exercise On Cognitive Functionmentioning
confidence: 99%
“…Accumulating scientific evidence supports the use of physical rehabilitation training and exercise as an effective nonpharmacologic therapy to improve motor symptoms, problems with mobility and gait (49,50), and non-motor features, including mood, cognition, and sleep [for review, see Reynolds et al (51)] for patients at all stages of PD. Intensive exercise may even induce neuroplastic disease-attenuating effects via endogenous production of neurotrophic factors, including BDNF (4,5,52,53).…”
Section: Discussionmentioning
confidence: 99%